PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP NILAI PERUSAHAAN (PBV) PADA PT ASTRA INTERNASIONAL TBK PERIODE 2013-2023 - Maria Seran, Livoni; Al-Choir, Fikron (Journal of Research and Publication Innovation, 2024)
This study aims to analyze the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on company value, measured using Price to Book Value (PBV) at PT Astra International Tbk during the period 2013-2023. The research method used is quantitative with a multiple linear regression approach. The data used are secondary data obtained from the company’s annual financial reports. The population in this study consists of all annual financial reports of PT Astra International Tbk published during the period 2013-2023. The research sample was selected using purposive sampling method. The results show that partially, the Current Ratio (CR) does not significantly affect PBV, with a coefficient value of -0.10007 and a p-value of 0.180 > 0.05 and t-statistic value of -1.453 < t-table 1.859. Debt to Equity Ratio (DER) significantly affects PBV, with a coefficient value of 0.4739030 and a p-value of 0.01 < 0.05 and t-statistic value of 15.691 > t-table 4.459. This indicates that the use of debt in the capital structure can increase company value. Simultaneously, the variables Current Ratio and Debt to Equity Ratio significantly affect PBV with an F-statistic value of 15.691 > F-table 4.459 and a p-value of 0.002 < 0.05. The contribution of CR and DER to PBV is 78.5%, while the remaining 21.5% is influenced by other variables not studied, which means that the combination of liquidity and capital structure plays an important role in determining company value in the stock market.